Metabolic profiling and gene expression analysis reveal the quality deterioration of postharvest toon buds between two different storage temperatures - Zhao, Hu; Shen, Cheng; Hao, Qingping; Fan, Mingqin; Liu, Xiaoli; Wang, Juan (Frontiers in Plant Science, 2023)
Toon buds, a popular woody vegetable, contain large amounts of nutrients. However, toon buds have strong respiratory metabolism after harvest and are highly prone to decay, resulting in quality deterioration. Low temperature can effectively inhibit postharvest senescence of toon buds. GC-TOF-MS combined with quantitative real-time PCR was used to elucidate the toon bud deterioration mechanism after harvest by analyzing the difference in the relative contents of primary metabolites and their derivatives, and the expression of key genes associated with metabolic pathways in toon buds between low temperature and room temperature storages for 72 h. Results showed that the ethylene synthesis in toon buds accelerated under room temperature storage, along with significant changes in the primary metabolic pathway. The catabolism of amino acids, fatty acids, and cell membrane phospholipids was accelerated, and the gluconeogenesis synthesis was strengthened. Moreover, the sucrose synthesis was increased, the glycolysis and TCA cycle were broken down, and the pentose phosphate pathway was vigorous. As metabolic intermediates, organic acids were considerably accumulated. Moreover, varieties of toxic compounds were produced in parallel with the activation of aromatic compounds. This work provided a comprehensive understanding of the metabolic regulation, thereby revealing how low and room temperatures differentially influenced the quality deterioration of postharvest toon buds.